A method for synthesis of polysubstituted 4-difluoromethyl and perfluoroalkyl pyrazoles. (9th April 2021) - Chen, Huahong; Wen, Shunli; Cui, Yubo; Lin, Lu; Zhang, Hanbang; Fang, Zheng; You, Yi; Weng, Zhiqiang
Abstract: A method for the synthesis of polysubstituted 4-difluoromethyl and perfluoroalkyl pyrazole derivatives by the Lewis acid- and base- co -mediated reaction of perfluoroacetyl diazoester with ketones is reported. A series of structurally diverse 4-difluoromethylated and perfluoroalkylated pyrazoles were obtained in moderate to good yields. The reactions proceeded smoothly under mild conditions with wide functional group tolerance. Graphical abstract: Image 1 Highlights: A method for synthesis of polysubstituted 4-difluoromethyl and perfluoroalkyl pyrazoles was developed. Various 4-difluoromethylated and perfluoroalkylated pyrazoles were obtained in moderate to good yields. A variety of functional groups were tolerated.